A Chicana feminist epistemology in adult education: A literature review - Cindy Peña; Jessica M. Quintero; Elizabeth Castañeda; Sonia Rey López (Adult Education Research Conference, 2020)
The purpose of this literature review was to identify research in adult education literature that used a Chicana feminist theoretical framework. The review was conducted using the Elton B. Stephen CO. (EBSCO) database. Although a thorough review of the most notable adult education journals revealed a lack of scholarly articles using Chicana Feminist Epistemology (CFE), the authors were able to identify three themes within the literature that could aid in incorporating CFE into adult education research. Future implications of embedding a Chicana feminist epistemology in adult education research and practice can create well-rounded studies centered around authentic Latina experiences.
Keywords: Chicana feminist epistemology; adult education research; Chicanas/Latinas; settlement houses